Differences in clinical manifestations and increased severity of systemic lupus erythematosus between two groups of Hispanics: European Caucasians versus Latin American mestizos (data from the RELESSER registry). (January 2020) - Hernández Cruz, B; Alonso, F; Calvo Alén, J; Pego-Reigosa, J M; López-Longo, F J; Galindo-Izquierdo, M; Olivé, A; Tomero, E; Horcada, L; Uriarte, E; Erausquin, C; Sánchez-Atrio, A; et al.
Background: Systemic lupus erythematosus (SLE) is regarded as a prototype autoimmune disease because it can serve as a means for studying differences between ethnic minorities and sex. Traditionally, all Hispanics have been bracketed within the same ethnic group, but there are differences between Hispanics from Spain and those from Latin America, not to mention other Spanish-speaking populations. Objectives: This study aimed to determine the demographic and clinical characteristics, severity, activity, damage, mortality and co-morbidity of SLE in Hispanics belonging to the two ethnic groups resident in Spain, and to identify any differences. Methods: This was an observational, multi-centre, retrospective study. The demographic and clinical variables of patients with SLE from 45 rheumatology units were collected. The study was conducted in accordance with Good Clinical Practice guidelines. Hispanic patients from the registry were divided into two groups: Spaniards or European Caucasians (EC) and Latin American mestizos (LAM). Comparative univariate and multivariate statistical analyses were carried out. Results: A total of 3490 SLE patients were included, 90% of whom were female; 3305 (92%) EC and 185 (5%) LAM. LAM patients experienced their first lupus symptoms four years earlier than EC patients and were diagnosed and included in the registry younger, and their SLE was of a shorter duration. The time in months from the first SLE symptoms to diagnosis was longer in EC patients, as were the follow-up periods. LAM patients exhibited higher prevalence rates of myositis, haemolytic anaemia and nephritis, but there were no differences in histological type or serositis. Anti-Sm, anti-Ro and anti-RNP antibodies were more frequently found in LAM patients. LAM patients also had higher levels of disease activity, severity and hospital admissions. However, there were no differences in damage index, mortality or co-morbidity index. In the multivariate analysis, after adjusting for confounders, in several models the odds ratio (95% confidence interval) for a Katz severity index >3 in LAM patients was 1.45 (1.038–2.026; p  = 0.02). This difference did not extend to activity levels (i.e. SLEDAI >3; 0.98 (0.30–1.66)). Conclusion: SLE in Hispanic EC patients showed clinical differences compared to Hispanic LAM patients. The latter more frequently suffered nephritis and higher severity indices. This study shows that where lupus is concerned, not all Hispanics are equal.